2008
DOI: 10.1247/csf.07037
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Tom1L1/Srcasm to Endosomes and the Midbody by Tsg101

Abstract: ABSTRACT. Tom1 (target of Myb 1) and its related proteins (Tom1L1/Srcasm and Tom1L2) constitute a protein family, which share an N-terminal VHS (Vps27, Hrs and STAM) domain and a following GAT (GGA and Tom1) domain. Tom1L1 has potential binding sequences for Tsg101, which is one of key regulators of the multivesicular body (MVB) formation. To obtain a clue to the role of Tom1L1 in the MVB formation, we have characterized the Tom1L1-Tsg101 interaction. We have found that not only the PTAP sequence in the GAT do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Recent studies have identified the presence of endosomal proteins including endosomal sorting complex required for transport proteins and Tom1L1 at the midbody during cytokinesis in which they function as regulators of mitotic cell division (Morita et al, 2007;Yanagida-Ishizaki et al, 2008). Interestingly, we observed that endogenous Vav2 protein localized to the central spindles of mitotic cells at telophase stage as well as at the midbody during cytokinesis in which it co-localized with the Tom1L1 protein (Thalappilly and Dusetti, unpublished results).…”
Section: Vav2 Regulates Egfr Stability S Thalappilly Et Almentioning
confidence: 52%
“…Recent studies have identified the presence of endosomal proteins including endosomal sorting complex required for transport proteins and Tom1L1 at the midbody during cytokinesis in which they function as regulators of mitotic cell division (Morita et al, 2007;Yanagida-Ishizaki et al, 2008). Interestingly, we observed that endogenous Vav2 protein localized to the central spindles of mitotic cells at telophase stage as well as at the midbody during cytokinesis in which it co-localized with the Tom1L1 protein (Thalappilly and Dusetti, unpublished results).…”
Section: Vav2 Regulates Egfr Stability S Thalappilly Et Almentioning
confidence: 52%
“…Although all Tom1 family members are capable of interacting with the ESCRT-0 component Hrs, only Tom1L1 interacts with the ESCRT-I component TSG101. Moreover, only Tom1 can associate with endofin, suggesting that the family members have both redundant and unique functions (Puertollano, 2005;Seet et al, 2004;Yanagida-Ishizaki et al, 2008). Further divergence in the Tom1 family occurs within the C-terminal region, in which Tom1 and Tom1L2 are most similar, whereas Tom1L1 shows less similarity (Fig.…”
Section: Cargo Sorting In the Endocytic Pathwaymentioning
confidence: 98%
“…The ESCRT 0 components Vps27 and Hse1 are both VHS domain-containing proteins, as are the Tom1 protein family (Puertollano, 2005;Raiborg and Stenmark, 2009). Recent evidence has been presented, in multiple and diverse eukaryotes, that Tom1 and related proteins bind ubiquitylated cargo (Blanc et al, 2009;Katoh et al, 2004) and the ESCRT I component Tsg101/Vps23 (Yanagida-Ishizaki et al, 2008). Consequently, it has been proposed that Tom1 proteins might have a role as central components of an ancient alternative ESCRT 0 machinery (Blanc et al, 2009).…”
Section: Tom1 Evolutionmentioning
confidence: 99%
“…The latter sequence-based approach was expanded to explore the representation of ESCRT machinery in available amoebozoan genomic databases. Recent evidence raised the possibility of an alternative ESCRT-0-like machinery centered on the Tom1 protein family (Blanc et al, 2009;Yanagida-Ishizaki et al, 2008). Tom1 family homologs have been identified in opisthokonts, as well as in Dictyostelium discoideum and the multicellular plants Arabidopsis thaliana and Oryza sativa (Blanc et al, 2009;Winter and Hauser, 2006).…”
mentioning
confidence: 99%